1987
DOI: 10.1111/j.1432-1033.1987.tb13636.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of binding equilibrium data by a variety of fitted isotherms

Abstract: Experimental binding equilibrium data, resulting from measurement of ligand binding to macromolecular carriers, are usually described by fitting of binding constants. These constants are often highly variable, as illustrated in the present paper by two examples, binding of salicylate to human serum albumin and of oxygen to hemoglobin. In order to avoid over-interpretation of binding constants it is pointed out that the best-fit solution, obtained by least-squares fitting, may be supplemented by several, e. g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…We have accordingly analyzed our data in terms of the general binding equation [24]. In the iterative evaluation of the stoichiometric constants it is possible to account for the stochastic errors on the experimental data [9]. We thus arrive at the conclusion that the affinity of albumin for fatty acids increases with chain length and decreases with temperature, in accordance with previous work by Spector et al [17] and by Ashbrook et al [25,26].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We have accordingly analyzed our data in terms of the general binding equation [24]. In the iterative evaluation of the stoichiometric constants it is possible to account for the stochastic errors on the experimental data [9]. We thus arrive at the conclusion that the affinity of albumin for fatty acids increases with chain length and decreases with temperature, in accordance with previous work by Spector et al [17] and by Ashbrook et al [25,26].…”
Section: Discussionsupporting
confidence: 76%
“…Calculations of binding constants by an iterative procedure were performed with a Digital PC 350 computer [9].…”
Section: Materials and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molar volumes were calculated according to V mol ϭ v ⅐M r . Error Analysis-95% confidence intervals for fitted parameters were estimated by the method of Broderson et al (38). Timasheff and co-workers (11,15) have shown that many low molecular weight osmolytes are excluded from the volumes immediately adjacent to proteins (i.e.…”
Section: -26)mentioning
confidence: 99%